Studi Komparasi Antara Penerapan Model Learning Cycle 5E dan Discovery Learning terhadap Capaian Keterampilan Proses Sains dan Hasil Belajar Kognitif Pada Siswa Kelas X SMA Negeri 3 Boyolali - Susilaningrum, Dian Fajarwati; Santosa, Slamet; Ariyanto, Joko (Universitas Sebelas Maret, 2017)
The purpose of this research is to determine the difference between the application of learning cycle 5E and discovery learning to the achievement of science process skills and cognitive outcomes and knowing a good model in trained the science process skills and improve cognitive outcomes of students class X SMA Negeri 3 Boyolali. The research is comparative with quantitative approach. Sample of class selected by cluster random sampling. Learning is carried out in two classes by applying the learning cycle 5E and discovery learning. Data collection techniques use tests, observations, and documentation. Normality and homogeneity test are performed as a requirement of hypothesis test. Hypothesis test used is t test with 5% significance level. Descriptive statistical test is conducted to know the average achievement of student cognitive outcomes. The research procedure includes planning, implementation and data analysis. The results showed a significant difference in the skills of the science process between the implementation of the learning cycle 5E with the discovery learning. Significant differences exist in the skills of observing, interpreting, experimenting and communicating. Scientific process skills on the aspects of grouping, formulating problems, preparing hypotheses do not show any significant differences. The insignificant differences were also shown in the students cognitive outcomes. The skills of observing, grouping, composing hypotheses, interpreting, experimenting, communicating, and cognitive outcomes have a higher achievement in the learning cycle 5E. The skill of formulating the problem has a higher achievement in the discovery learning. The conclusion is there is difference between the application of learning cycle 5E with discovery learning to the achievement of science process skill and cognitive outcomes of grade X students of SMA Negeri 3 Boyolali. Learning cycle 5E and discovery learning have their respective sensitivity in trained the science process skills and improve students cognitive outcomes.science process skill, cognitive outcomes, learning cycle 5E, discovery learning